2023
DOI: 10.1037/emo0001083
|View full text |Cite
|
Sign up to set email alerts
|

From values to emotions: Cognitive appraisal mediates the impact of core values on emotional experience.

Abstract: Emotions and values are fundamentally connected. They both are psychological markers of subjective relevance and are thought to be deeply functionally intertwined: According to appraisal theories of emotion, emotions arise when value concerns are at stake; according to theories of value, a value that is threatened or supported gets infused with feelings. Surprisingly, while these assumptions are considered well established by researchers in the respective domains, up to now, empirical research has not provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
(113 reference statements)
0
10
0
Order By: Relevance
“…The emotions literature suggests that situations involving important values can easily give rise to emotional reactions, which subsequently guide behavior. For example, across three experiments, Conte et al (2023) demonstrated that reactions were stronger for negative stimuli than positive stimuli—because negative stimuli aroused negative emotions from individuals. Similar results are found in the neuropsychology literature, suggesting that negative information, as opposed to neutral information, increases both arousal and threat perceptions (Krasowski et al, 2021).…”
Section: Prevalence Of Political Informationmentioning
confidence: 99%
“…The emotions literature suggests that situations involving important values can easily give rise to emotional reactions, which subsequently guide behavior. For example, across three experiments, Conte et al (2023) demonstrated that reactions were stronger for negative stimuli than positive stimuli—because negative stimuli aroused negative emotions from individuals. Similar results are found in the neuropsychology literature, suggesting that negative information, as opposed to neutral information, increases both arousal and threat perceptions (Krasowski et al, 2021).…”
Section: Prevalence Of Political Informationmentioning
confidence: 99%
“…Values can thus be conceptualized as lenses that weight the pertinence of new information and guide their appraisal at onset (Scherer, 2013;Schwartz and Bilsky, 1987). New information appraised as value-relevant directs attention in a noisy environment and elicits stronger emotional reactions than value-irrelevant information (Conte et al, 2022). Biospheric values in particular have been related to more intense emotional responses towards positive and negative information concerning nature and climate change (Conte et al, 2022), and to an individual disposition to experience emotions in an environmental context (Hahnel and Brosch, 2018).…”
Section: The Role Of Values In Technology Evaluation and Information ...mentioning
confidence: 99%
“…New information appraised as value-relevant directs attention in a noisy environment and elicits stronger emotional reactions than value-irrelevant information (Conte et al, 2022). Biospheric values in particular have been related to more intense emotional responses towards positive and negative information concerning nature and climate change (Conte et al, 2022), and to an individual disposition to experience emotions in an environmental context (Hahnel and Brosch, 2018). This suggests that biospheric values might enhance the updating of affective associations to energy technologies: in other words, accumulating information about a value-relevant energy technology should lead to more extreme affective reactions.…”
Section: The Role Of Values In Technology Evaluation and Information ...mentioning
confidence: 99%
See 2 more Smart Citations